History of university ophthalmology in Wroclaw in 1812-2002 years - Niżankowska, Maria Hanna; Muzyka-Woźniak, Maria; Oficjalska-Młyńczak, Jolanta; Adamiec, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2002)
The authors present the history of the Department of Ophthalmology in Wrocław since 1812. Special attention is paid to following professors of ophthalmology and Directors of the Univeristy Eye Hospital: T. V. G. Benedict, A. T. Mitteldorf, R. Foerster, H. L. Cohn, H. Magnus, A. Groenouw, H. Wilbrand, W. Uhthoff, Th. Axenfeld, G. Lenz, A. Bielschowsky, W. Dieter, A. Bednarski, J. M. Grzędzielski, L. Hirschfeld, W. J. Kapuściński, S. Drozdowska, E. Ogielska, A. Huszcza, L. Baran, P. Hańczyc, M. H. Niżankowska.